Differential susceptibility to tetracycline, oxytetracycline and doxycycline of the calf pathogens Mannheimia haemolytica and Pasteurella multocida in three growth media. Issue 1 (28th September 2018) - Mead, Andrew; Lees, Peter; Mitchell, John; Rycroft, Andrew; Standing, Joseph F.; Toutain, Pierre‐Louis; Pelligand, Ludovic
Abstract: For clinical isolates of bovine Mannheimia haemolytica and Pasteurella multocida, this study reports minimum inhibitory concentration (MIC) differences for tetracycline, oxytetracycline and doxycycline between cation‐adjusted Mueller‐Hinton broth (CAMHB), foetal bovine serum (FBS) and Roswell Park Memorial Institute (RPMI) medium. MICs were determined according to CLSI standards and additionally using five overlapping sets of twofold dilutions. Matrix effect : (a) free drug MICs and minimum bactericidal concentrations (MBC) for all drugs were significantly higher in FBS than in CAMHB for both pathogens ( p < 0.001); (b) MICs and MBCs were higher for CAMHB and FBS compared to RPMI for P. multocida only. Net growth rate for P. multocida in CAMHB was significantly slower than in FBS and higher than in RPMI, correlating to MIC and MBC ranking. Drug effect : doxycycline MICs and MBCs were significantly lower ( p < 0.001) in both CAMHB and FBS than tetracycline and oxytetracycline for both pathogens. Only for M. haemolytica were oxytetracycline MIC and MBC significantly lower than tetracycline, precluding the use of tetracycline to predict oxytetracycline susceptibility in this species. Determining potencies of tetracyclines in a physiological medium, such as FBS, is proposed, when the objective is correlation with pharmacokinetic data for dosage determination.